2022
DOI: 10.1021/acschemneuro.1c00819
|View full text |Cite
|
Sign up to set email alerts
|

Ferristatin II, an Iron Uptake Inhibitor, Exerts Neuroprotection against Traumatic Brain Injury via Suppressing Ferroptosis

Abstract: As a specific ferroptosis marker, transferrin receptor 1 (TfR1) expression is increased following traumatic brain injury (TBI), but the precise role of TfR1 in TBI-induced ferroptosis and neurodegeneration remains to be determined. To further identify more potent ferroptosis inhibitors and effective targets for treating TBI, our study aims at investigating the effects of TfR1 on ferroptosis in a mouse TBI model using ferristatin II (an iron uptake and TfR1 inhibitor). The effect of ferristatin II was first ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The use of mir-212-5p in the CCI mouse model can target PTGS2 to reduce ferroptosis and protect the brain [123]. Moreover, Cheng et al [124] found that the use of iron uptake inhibitor ferristatin II in mouse model with TBI can inhibit the formation of iron proteasomes and alleviate TBI injury in brain. For a long time, due to the lack of clear understanding, the treatment of TBI is very difficult.…”
Section: Ferroptosis In Tbimentioning
confidence: 99%
“…The use of mir-212-5p in the CCI mouse model can target PTGS2 to reduce ferroptosis and protect the brain [123]. Moreover, Cheng et al [124] found that the use of iron uptake inhibitor ferristatin II in mouse model with TBI can inhibit the formation of iron proteasomes and alleviate TBI injury in brain. For a long time, due to the lack of clear understanding, the treatment of TBI is very difficult.…”
Section: Ferroptosis In Tbimentioning
confidence: 99%
“…The brain shows a high vulnerability to excessive ROS production due to low antioxidants and high metabolism. Intracerebral oxidative injury is presented primarily as lipid peroxidation due to the increase in the content of polyunsaturated fatty acids within the membrane-abundant structure [ 47 ]. Lipid peroxides will degrade to toxic aldehydes such as 4-HNE and malonaldehyde, thus affecting cell membrane permeability and fluidity.…”
Section: Discussionmentioning
confidence: 99%
“…Ruxolitinib was found to protect against neuronal ferroptosis in a mouse TBI model [142]. Ferristatin II, an iron uptake inhibitor, prevents neuronal ferroptosis after TBI [143], while tetrandrine ameliorates TBI by regulating autophagy to reduce ferroptosis [144].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%